ANALISIS DESKRIPTIF TINGKAT PERILAKU PROKRASTINASI AKADEMIK SISWA KELAS X MIPA - Rusdana, Nita Laila; Fitriana, Siti; Mujiono, Mujiono (Jurnal Empati Bimbingan dan Konseling, 2022)
Abstract. Academic procrastination behavior is the behavior of procrastinating to do academic tasks that is done intentionally and repeatedly. Academic procrastination behavior can also adversely affect student achievement. This study aims to determine the level of academic procrastination behavior of class X Mipa students at SMAN 1 Bae Kudus. This type of research is quantitative research with a descriptive approach. The population in this study consisted of 250 students and the samples taken were 214 students. Data analysis in this study was obtained through a student academic procrastination questionnaire consisting of 35 closed statement items with 4 alternative answers. The results obtained in this study indicate that the level of academic procrastination behavior of class X Mipa students at SMAN 1 Bae Kudus is "low" with an average of 74.39.Keywords: Academic Behavior Level ProcrastinationÂ Abstrak. Perilaku prokrastinasi akademik merupakan perilaku menunda-nunda untuk mengerjakan tugas akademik yang dilakukan secara sengaja dan berulang-ulang. Perilaku prokrastinasi akademik juga dapat berpengaruh buruk terhadap prestasi siswa.Â  Penelitian ini bertujuan untuk mengetahui tingkat perilaku prokrastinasi akademik siswa kelas X Mipa SMAN 1 Bae Kudus. Jenis penelitian ini adalah penelitian kuantitatif dengan pendekatan deskriptif. Populasi dalam penelitian ini terdiri dari 250 siswa dan sampel yang diambil yaitu sebanyak 214 siswa. Analisis data dalam penelitian ini diperoleh melalui kuesioner prokrastinasi akademik siswa yang terdiri dari 35 butir pernyataan tertutup dengan 4 alternatif jawaban. Hasil yang diperoleh dalam penelitian ini menunjukkan bahwa tingkat perilaku prokrastinasi akademik siswa kelas X Mipa SMAN 1 Bae Kudus adalah â€œrendahâ€ dengan rata-rata 74,39.Kata kunci: Akademik Perilaku Prokrastinasi TingkatÂ